''Nec spe nec metu'' y otras empresas o divisas de Felipe II - López Poza, Sagrario; Zafra, Rafael; Azanza López, José Javier, 1968- (Pamplona: Universidad de Navarra, 2011)
Se ofrece información y análisis de las empresas o divisas empleadas por el rey español Felipe II, especialmente la que empleó con más asiduidad: "Nec spe nec metu".
We offer information and analysis about the imprese, devices or badges used by the Spanish King Philip II, especially the one used more frequently: “Nec spe nec metu”.
Keywords: Felipe‏ -- II, -- Rey de España; Emblemas; Cambio exterior